Genetic aberrations and molecular biology of cardiac sarcoma. (May 2020) - Urbini, Milena; Astolfi, Annalisa; Indio, Valentina; Nannini, Margherita; Pizzi, Carmine; Paolisso, Pasquale; Tarantino, Giuseppe; Pantaleo, Maria Abbondanza; Saponara, Maristella
Cardiac tumors are rare and complex entities. Early assessment and differentiation between non-neoplastic and neoplastic masses, be they benign or malignant, is essential for guiding diagnosis, determining prognosis, and planning therapy. Cardiac sarcomas represent the most frequent primary malignant histotype. They could have manifold presentations so that the diagnosis is often belated. Moreover, considering their rarity and the limitation due to the cardiac location itself, the optimal multimodal management of patients affected by primary cardiac sarcomas still remains highly difficult and outcome dismal. Therefore, there is an urgent need to improve these results mainly focusing on more adequate tools for prompt diagnosis and exploring new and more effective therapies. Knowledge about the molecular landscape and pathogenesis of cardiac sarcoma is even more limited due to the rarity of this disease. In this sense, the molecular characterization of heart tumors could unfold potentially novel, druggable targets. In this review, we focused on genetic aberrations and molecular biology of cardiac sarcomas, collecting the scarce information available and resuming all the molecular findings discovered in each tumor subtype, with the aim to get further insights on mechanisms involved in tumor growth and to possibly highlight specific molecular profiles that can be used as diagnostic tests and unveil new clinically actionable targets in this tricky and challenging disease.